NASH-CHECK patient-reported outcome instrument: evaluation of content and face validity for patients with metabolic dysfunction–associated steatohepatitis and compensated cirrhosis - Lynda C. Doward; Matthew Breckons; Maria-Magdalena Balp; James Twiss; Luke Vale; Lorraine McSweeney; Clifford A. Brass; Quentin M. Anstee; Arun J. Sanyal (Journal of Patient-Reported Outcomes)
Abstract Background NASH-CHECK is a patient-reported outcome measure (PROM) that assesses symptoms and broader health-related quality of life (HRQOL) impacts of metabolic dysfunction–associated steatohepatitis (MASH), previously called non-alcoholic steatohepatitis (NASH). The measure was initially developed and validated for patients with non-cirrhotic MASH. This study describes an evaluation of the suitability of NASH-CHECK for patients with compensated cirrhotic MASH. Methodology Concept elicitation (CE) interviews were conducted with patients with clinically confirmed compensated cirrhotic MASH in the United States (US) and United Kingdom (UK) to determine the symptom burden and broader HRQOL impact of MASH. Symptoms and broader HRQOL impacts identified during analysis of the CE data were compared with the key concepts included in NASH-CHECK; any symptoms reported in the CE interviews but not reflected in NASH-CHECK were reviewed for relevance by clinical experts. The content validity of NASH-CHECK was evaluated further via cognitive debriefing (CD) interviews conducted with patients with compensated cirrhotic MASH in the US and UK. Results CE interviews were conducted with 33 patients with compensated cirrhotic MASH (US = 9, UK = 24; 60.6% female; mean age, 64.3 years). Key symptoms described were similar to those reported by patients with non-cirrhotic MASH identified during the development of NASH-CHECK; these included abdominal pain, abdominal bloating, itch, fatigue, sleeping difficulties, and cognitive symptoms. Other key HRQOL impacts included activity limitations and emotional, social, relationship, and work impacts. All key symptom and broader HRQOL impacts reported by patients with compensated cirrhotic MASH are currently included in NASH-CHECK, and no additional symptoms or HRQOL impacts reported during the CE interviews were deemed relevant for inclusion. CD interviews were conducted with 17 patients with compensated cirrhotic MASH (US = 8, UK = 9; 47.1% female; mean age, 62.8 years). Patient feedback on NASH-CHECK content confirmed that the concepts captured by the items were considered important, relevant, and comprehensive for addressing the impact of compensated cirrhotic MASH. Conclusions The results support the content validity of NASH-CHECK for patients with compensated cirrhotic MASH, demonstrating that NASH-CHECK is a suitable PROM for use in clinical trials, studies, and practice for this patient population.